Solution of partial differential equations by new double integral transform (Laplace - Sumudu transform) - Shams A. Ahmed (Elsevier, 2021)
The primary purpose of this research is to demonstrate an efficient new double transform mentioned since the double Laplace - Sumudu transform (DLST) solve partial differential equations. The theorems handling fashionable properties of the double Laplace - Sumudu transform are proved, the convolution theorem with evidence is mentioned, then, via the usage of these outcomes the solution of partial differential equations is made. The results showed that the double Laplace - Sumudu transform was more efficient and useful to handle such these kinds of equations.